Challenges and Opportunities of Small Countries for Integration into the Global Economy, as a Case of Mongolia - Lhamsuren Nyamtseren (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2004)
This paper examines the impacts of globalization on small countries, covering the main features of globalization, the quality of national economic and commercial environment, main characteristics of small countries including important facts and concrete indicators for their development, and their challenges and opportunities for regional integration. It concludes that: 1) globalization is a process of continuing integration of the countries of the world that is beneficial, inevitable and irreversible. No any country can afford to remain isolated from the world economy. 2) some of small countries might have higher income and much richer than others. But all small countries do not posse such an advantage. Therefore, the small countries were in this paper differently considered according to their per capita income level which varies significantly from each others. 3) For most developing countries, in particular the small and poor countries, a North-South Regional Integration Agreement with a large industrial country is likely to be superior to a South-South Regional Integration Agreement with a developing or poor small country.
Keywords: F02; F43; F21; F15; 330; Globalization; small countries; economic integration; income distribution; Kleines-offenes-Land; Kleines-Land-Modell; Globalisierung; Handelsregionalismus; Nord-Süd-Beziehungen; Welt; Mongolei